Application of Mathematica Software to Solve Pulp Washing Model. (29th December 2013) - Kumar, Jitender; Ganaie, Ishfaq A.; Kukreja, Vijay K.
Abstract : The removal of the bulk liquor surrounding the pulp fibers using less concentrated liquor is known as pulp washing. In the present study, a pulp washing model involving diffusion-dispersion through packed beds of finite length is presented. Separation of variables is applied to solve system of governing partial differential equations and the resulting equations are solved using Mathematica. Results from the present case are compared with those of previous investigators. The present case is giving better results than the previous investigators.